IMPLEMENTASI EKSTRAKULIKULER MUHADHOROH DALAM PEMBENTUKAN KARAKTER SISWA DI MTS BUSTANUL ULUM LAMPUNG TENGAH - Ramadani, Bagus; Baharudin; Uswatun Hasanah, Ida Faridatul Hasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this research is to investigate how MTs Bustanul Ulum, Central Lampung, uses the Muhadhoroh extracurricular activity to develop students' character. Observation, in-depth interviews, and documentation were used to gather data for this descriptive qualitative study. The results indicate that the Muhadhoroh activity is systematically prepared through thematic planning, activity scheduling, and the involvement of Islamic education teachers as facilitators. Task division is carried out via a student-based mini organizational structure that fosters values of responsibility, leadership, cooperation, and discipline. Muhadhoroh has proven to positively influence character development across cognitive, affective, and psychomotor domains. Active student involvement at every stage transforms Muhadhoroh into a contextual, spiritual, and applicable learning medium. This study concludes that Muhadhoroh serves not only as a platform for language skills enhancement but also as a character education instrument rooted in Islamic values. Keywords: Muhadhoroh, extracurricular, character building, Islamic education